2010
DOI: 10.1001/archinternmed.2010.79
|View full text |Cite
|
Sign up to set email alerts
|

Nut Consumption and Blood Lipid Levels

Abstract: Nut consumption improves blood lipid levels in a dose-related manner, particularly among subjects with higher LDL-C or with lower BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
156
6
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 374 publications
(179 citation statements)
references
References 51 publications
16
156
6
1
Order By: Relevance
“…When compared with control diets, walnut-rich diets resulted in a significantly greater decrease in total and LDL-cholesterol concentrations, with weighted mean decreases of 10.3 and 9.2 mg/dL, respectively. The overall result indicated that the walnut diets compared with the control diets were associated with a 6.7% greater decrease in LDL-cholesterol concentration, which concurs with the mean 7% decrease reported with various nut types in the pooled analysis [69]. HDL-cholesterol and triglycerides were not significantly affected by walnut diets more than by control diets.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fsupporting
confidence: 79%
See 4 more Smart Citations
“…When compared with control diets, walnut-rich diets resulted in a significantly greater decrease in total and LDL-cholesterol concentrations, with weighted mean decreases of 10.3 and 9.2 mg/dL, respectively. The overall result indicated that the walnut diets compared with the control diets were associated with a 6.7% greater decrease in LDL-cholesterol concentration, which concurs with the mean 7% decrease reported with various nut types in the pooled analysis [69]. HDL-cholesterol and triglycerides were not significantly affected by walnut diets more than by control diets.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fsupporting
confidence: 79%
“…A Mediterranean diet supplemented with 30 g of mixed nuts (walnuts, almonds and hazelnuts) per day also showed beneficial effects on the lipid profile compared with advice on a low-fat diet in diabetic and non diabetic participants in the PREDIMED study, a randomized trial of dietary intervention for the primary prevention of cardiovascular disease [80]. Of note, two randomized trials that used cashews or walnuts [81] and mixed nuts [82] compared to control diets in obese patients with the metabolic syndrome failed to show the predictable cholesterol lowering-effect, which supports the findings of the pooled analysis [69] (Figure 3) regarding the inverse association between cholesterol responses to nut feeding and BMI. There may be a mechanistic explanation for decreased lipid responsiveness to dietary intervention in patients with the metabolic syndrome.…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 59%
See 3 more Smart Citations